REASONABLE ACCOMMODATION FOR PERSONS WITH DISABILITIES (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
The reasonable accommodation duty is an element of the principal of non-discrimination embedded inter alia in the United Nations Convention on the Rights of Persons with Disabilities. It is stated that reasonable accommodation means necessary and appropriate modification and adjustments not imposing a disproportionate or undue burden, where needed in a particular case, to ensure to persons with disabilities the enjoyment or exercise, on an equal basis with others, of all human rights and fundamental freedoms. In addition, by placing the reasonable accommodation duty within the definition of discrimination the Convention introduces a premise that exercising the fundamental rights needs individualized measures aimed at resolving the existing systemic discrimination against persons with disabilities.  However, there is no unified stand worldwide as for how unjustified denial of such accommodations is treated, i.e. whether it is considered as a form of direct discrimination or indirect discrimination, or sui generis form of discrimination. This paper explores this venue using comparative observations from the EU Member States. Furthermore, the paper elaborates on the elements of the reasonable accommodation and determines its frames in the national legal context, especially exploring the remits of the new Law on Prevention and Protection from Discrimination (2019). Finally, the paper presents ways forward in increasing the importance of this legal institute in strengthening the fundamental rights of persons with disabilities. The text uses examples from national and international jurisprudence as well as reports and analysis that have been developed on the same subject matter.